Meningkatkan hasil belajar siswa pada materi penjumlahan pecahan melalui media wordwall quis game dikelas V SDN 17 LIMBOTO - Dina; Yusraningsih H. Pongoliu; Yulanti S. Mooduto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improvstudents’learning outcomes on the material of adding fractions through a media. Wordwall quiz game in class V SDN 17 Limboto. The type of research used in this study is classroom action research with research subjectof 31 students of class V SDN 17 Limboto. This study uses observation techniques, tests, and documentation. Data analysis techniques are teacher activities, student activities and student activities and student learning outcomes with indicators ≥ 85%. The study was conducted in two cycles, cycle I consisted of three meetings, while cycle II consisted of one meeting with four stages, namely: preparation stage, action implementation stage, monitoring and evaluation stage, analysis and reflection stage. The results of the research on the initial observation were only 13 students or 42% who achieved the minimum completeness criteria (MCC). In cycle I, the number of students with anincrease in learning outcomes was 25 students (80.64%). Furthermore, in cycle II, the increase in student learning outcomes reached 28 students (90.32%). Based on the results of the research and discussion, it can be concluded that using the word wall quis game learning media can improve student learning outcomesin the addition of fractions material for class V SDN 17 Limboto. It is hoped that schools can support the implementation of wordwall media as an effort to improve the quality of learning, through this media it cah help schools create a more interesting, innovative learning atmosphere, and utilize technology as part of the modern education process.